Surgical management of insulinoma over three decades. Issue 12 (December 2021) - de Carbonnières, Anne; Challine, Alexandre; Cottereau, Anne Ségolène; Coriat, Romain; Soyer, Philippe; Abou Ali, Einas; Prat, Frédéric; Terris, Benoit; Bertherat, Jérôme; Dousset, Bertrand; Gaujoux, Sébastien
Abstract: Background: This paper reports our experience of the perioperative management of patients with sporadic, non-malignant, pancreatic insulinoma. Methods: A retrospective monocentric cohort study was performed from January 1989 to July 2019, including all the patients who had been operated on for pancreatic insulinoma. The preoperative work-up, surgical management, and postoperative outcome were analyzed. Results: Eighty patients underwent surgery for sporadic pancreatic insulinoma, 50 of which were female (62%), with a median age of 50 (36–70) years. Preoperatively, the tumors were localized in 76 patients (95%). Computed tomography (CT) and magnetic resonance imaging allowed exact preoperative tumor localization in 76% of the patients (64–85 and 58–88 patients, respectively), increasing to 96% when endoscopic ultrasonography was performed. Forty-one parenchyma-sparing pancreatectomies (PSP) (including enucleation, caudal pancreatectomy, and uncinate process resection) and 39 pancreatic resections were performed. The mortality rate was 6% (n = 5), with a morbidity rate of 72%, including 24 severe complications (30%) and 35 pancreatic fistulas (44%). No differences were found between formal pancreatectomy and PSP in terms of postoperative outcome procedures. The surgery was curative in all the patients. Conclusion: CT used in combination with endoscopic ultrasonography allows accurate localization of insulinomas in almost all patients. When possible, a parenchyma-sparing pancreatectomy should be proposed as the first-line surgical strategy.